2014
DOI: 10.1038/ncomms4198
|View full text |Cite
|
Sign up to set email alerts
|

Biskyrmion states and their current-driven motion in a layered manganite

Abstract: The magnetic skyrmion is a topologically stable spin texture in which the constituent spins point to all the directions wrapping a sphere. Generation and control of nanometric magnetic skyrmions have large potential, for example, reduced power consumption, in spintronics device applications. Here we show the real-space observation of a biskyrmion, as defined by a molecular form of two bound skyrmions with the total topological charge of 2, realized under magnetic field applied normal to a thin plate of a bilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
293
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 278 publications
(309 citation statements)
references
References 33 publications
15
293
0
1
Order By: Relevance
“…The green and red regions shown in Figure 2b correspond to in-plane anti-parallel magnetic domains, while the black regions represent the out-of plane magnetic domains. The revolving behavior of the biskyrmions under a vertical magnetic field is similar to that reported previously [5,7,8,21,22] . The dynamics of formation and disappearance of the biskyrmions with increasing applied magnetic field were successfully recorded by using insitu Lorentz TEM (see Supplementary Movie, SI).…”
supporting
confidence: 89%
See 3 more Smart Citations
“…The green and red regions shown in Figure 2b correspond to in-plane anti-parallel magnetic domains, while the black regions represent the out-of plane magnetic domains. The revolving behavior of the biskyrmions under a vertical magnetic field is similar to that reported previously [5,7,8,21,22] . The dynamics of formation and disappearance of the biskyrmions with increasing applied magnetic field were successfully recorded by using insitu Lorentz TEM (see Supplementary Movie, SI).…”
supporting
confidence: 89%
“…clearly indicates that each spin configuration is composed of two single skyrmions with opposite magnetic helicities; that is, each skyrmion has clockwise (CW) and counterclockwise (CCW) spin curls with an out-of-plane magnetization culminating at the core. This spin configuration is the same as that of biskyrmions reported by Yu et al [22] with N s =2. We define the polarity of constituent skyrmions as plus (+) for CW skyrmions and minus (-) for CCW skyrmions.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Since this initial discovery there has been tremendous growth in the field as an increasing number of materials have been found that can support a skyrmion phase [3][4][5][6][7][8][9][10] . There are also numerous proposals on how to stabilize skyrmion states by utilizing different materials properties or bilayers [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%